Pragmatic Language Level in Autism Spectrum Disorders from the Perspective of Speech and Language Therapy in the Czech Republic - Vitásková, Kateřina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The objective is an overview of the partial research outcomes aimed at evaluating the pragmatic level of communication (PCL) in persons with autism spectrum disorder (ASD) from the perspective of speech and language therapy (SLT) in the Czech Republic, where the SLT system is divided into three different sectors bringing specific views on their concept. A partial objective is to highlight the need to create specific SLT diagnostic materials for national- relevant use and outline their concept. It is based on a brief theoretical analysis of the current state of knowledge, and presents the quantitative and qualitative outcomes based on a mixed research design. Partial results confirm the lack of practical SLT´s focus on the area of PCL diagnosis in ASD, the lack of relevant diagnostic materials as well as effective options of SLT  intervention in PCL of people with (ASD) focusing on selected individually impaired factors.